Chronic Administration of 5-HT1A Receptor Agonist Relieves Depression and Depression-Induced Hypoalgesia - Zhao-Cai Jiang; Wei-Jing Qi; Jin-Yan Wang; Fei Luo (The Scientific World Journal)
Previous studies have shown that depressed patients as well as animal models of depression exhibit decreased sensitivity to evoked pain stimuli, and serotonin is indicated to be involved in depression-induced hypoalgesia. The purpose of this study was to investigate the potential role of 5-HT1A receptor in the depression-induced hypoalgesia. Acute or chronic administration of 5-HT1A receptor agonist, 8-OH-DPAT, was performed in olfactory bulbectomy (OB) and sham-operated rats. The depression-like behavior and pain thresholds were measured using open-field test and radiant heat thermal pain test, respectively. We found that acute administration of 8-OH-DPAT increased locomotor activity and pain thresholds in the sham rats but had no effect on the OB rats. In contrast, chronic administration of 8-OH-DPAT reduced locomotor activity and pain thresholds and restored them to normal level. Increased pain thresholds were also observed in the sham rats after the chronic administration. These results demonstrated that chronic administration of 8-OH-DPAT reversed the depression-induced decrease in pain sensitivity in rats, suggesting that 5-HT1A receptor may play a role in the depression-associated hypoalgesia.